The Kakawin Siwaratrikalpa by Mpu Tanakun: Saivistic Orthodoxy and Orthopraxis - W.A. Sindhu Gitananda (IAHN-TP Palangka Raya, 2026)
Mpu Tanakun’s Kakawin Siwaratrikalpa is a fascinating text to explore further to gain insight into the religious phenomena of Balinese Hinduism. This article focuses on the Siva-centric discourse found within this literary work. The research method employed is qualitative, utilizing a hermeneutic and comparative perspective between literature as a form of orthodoxy and religious rituals as a manifestation of orthopraxis. The findings reveal that the pursuit of Lubdhaka culminates in forgiveness within a simple and meditative Saivistic path, thereby achieving full awareness in the darkest night, leading toward the light—or Siva himself. Therefore, the Kakawin Siwaratrikalpa offers another alternative path, primarily through the Siwaratri ritual, which is orthopraxis in nature, without losing the meaning and value of Siva-ness itself yet is more meditative.